2011
DOI: 10.33225/pec/11.36.51
|View full text |Cite
|
Sign up to set email alerts
|

Popularity of Sport Among Pupils of Primary Schools in Serbia

Abstract: The aim of this study was to determine which sports are most popular among pupils of primary school in Serbia, in order to determine which sports would be advisable to introduce in the classes of physical education to increase the level of interest of pupils to actively participate in PE. The sample included 8120 students, of which 30% are actively involved in sports, 28 % drop out and 42% had never engaged in sports. Most students would like to introduce as an optional sport basketball, swimming, volleyball, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 8 publications
4
6
0
Order By: Relevance
“…The sports that the schoolchildren in Serbia would like to participate in most were soccer, basketball, swimming, and volleyball, which is in agreement with the results obtained by Višnjić and Sretenović (2014) which indicated that schoolchildren would like more access to swimming, soccer, volleyball, tennis, and basketball. Radojević et al (2011) determined a preference for basketball, swimming, volleyball, and soccer, and Milanović and Radisavljević-Janić (2011), who worked with a sample of schoolchildren from Belgrade, concluded that schoolchildren mostly took part in basketball, volleyball, and soccer. Ilić et al (2012) concluded that schoolchildren would welcome the introduction of swimming, soccer, basketball, and volleyball into the school curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sports that the schoolchildren in Serbia would like to participate in most were soccer, basketball, swimming, and volleyball, which is in agreement with the results obtained by Višnjić and Sretenović (2014) which indicated that schoolchildren would like more access to swimming, soccer, volleyball, tennis, and basketball. Radojević et al (2011) determined a preference for basketball, swimming, volleyball, and soccer, and Milanović and Radisavljević-Janić (2011), who worked with a sample of schoolchildren from Belgrade, concluded that schoolchildren mostly took part in basketball, volleyball, and soccer. Ilić et al (2012) concluded that schoolchildren would welcome the introduction of swimming, soccer, basketball, and volleyball into the school curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…The system of dependent variables includes the following selection of sports: athletics, aerobics, aikido, acrobatics, badminton, cycling, judo, fitness, soccer, gymnastics, karate, basketball, volleyball, orienteering, swimming, rhythmic gymnas-tics, handball, wrestling, synchronised swimming, skiing, sports dancing, table tennis, archery, taekwondo, tennis, water polo, and rowing. The list of sports was based on previous, select research (Radojević et al, 2011;Ilić et al 2012;Ilić, 2013).…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Achieving sustainability in the long run via building a membership base is only possible when organizations have well-functioning marketing aimed at gaining attention and reaching and recruiting new athletes from an early age [13,53]. It is an emphasis on this dimension of sustainability that makes it crucial to study the perceived popularity of different sports among the population depending on their age.…”
Section: The Sustainability Of Sports Organizations and Their Sustain...mentioning
confidence: 99%
“…The authors of this study identified not only the favorite sports among the children, but they also proved that there were statistically significant differences in preferences in relation to genders. As they studied a different population, the question is whether a similar statistical difference would appear in the Slovak Republic [13].…”
Section: Introductionmentioning
confidence: 99%